2016
DOI: 10.4236/ojms.2016.62025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sudden Stratospheric Warming Events on the Distribution of Total Column Ozone over Polar and Middle Latitude Regions

Abstract: In winter the polar stratosphere is extremely cold. During the Sudden Stratospheric Warming events, the polar stratospheric temperature rises concurrently zonal-mean zonal flow weakens over a short period of time. As the zonal flow weakens, the stratospheric circulation becomes highly asymmetrical and the stratospheric polar vortex is displaced off the pole. The polar stratospheric temperature rises by 50˚C and the stratospheric circumpolar flow reverses direction in a span of just few days. Sudden Stratospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Some studies of long-term variations of the protective ozone layer at mid-latitudes in the Northern Hemisphere and in particular over Bulgaria in recent decades show that it is relatively stable, with no significant trends being observed [2,12]. It is well known that the strongest short-term variations in ozone concentration and total stratospheric ozone are observed during the winter seasons, especially during Sudden Stratospheric Warming [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies of long-term variations of the protective ozone layer at mid-latitudes in the Northern Hemisphere and in particular over Bulgaria in recent decades show that it is relatively stable, with no significant trends being observed [2,12]. It is well known that the strongest short-term variations in ozone concentration and total stratospheric ozone are observed during the winter seasons, especially during Sudden Stratospheric Warming [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of long-term variations of the protective ozone layer at mid-latitudes in the Northern Hemisphere and in particular over Bulgaria in recent decades show that it is relatively stable, with no significant trends being observed [2,12]. It is well known that the strongest short-term variations in ozone concentration and total stratospheric ozone are observed during the winter seasons, especially during Sudden Stratospheric Warming [13]. Stratospheric warmings are large-scale anomalies in the winter regime of the stratosphere which cause strong variations in temperature, pressure, and wind speed without any external factor being identified for their occurrence and without the presence of any additional energy into the stratosphere [14].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relatively long radioactive half-life (53.22 d) and its cosmogenic origin in the upper troposphere and lower stratosphere (UT-LS) (Lal and Peters, 1967), 7 Be is considered a tracer for intrusion of stratospheric air into the troposphere and large-scale subsidence (e.g., Liu et al, 2016;Chae and Kim, 2019;Heikkila et al, 2008). The variability of the 7 Be activity concentration in surface layers is driven by both static and dynamic factors, e.g., geographical location of the monitoring sites (e.g., Hernández-Ceballos et al, 2015), seasonal atmospheric processes driving transport of carrier aerosols (Lal and Peters, 1967), stratosphere-troposphere air mass exchange (Cristofanelli et al, 2003(Cristofanelli et al, , 2009Putero et al, 2016;Brattich et al, 2017a), synoptic influences (Usoskin E. Be concentration events at the surface in northern Europe et al, 2009), downward transport in the troposphere (Lee et al, 2007), solar activity, and dry and wet deposition (e.g., Hernández-Ceballos et al, 2015, 2016Ioannidou and Papastefanou, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Further, over the last decade many studies have investigated the 7 Be records in northern Europe (Leppänen et al, 2010(Leppänen et al, , 2012Leppänen and Paatero, 2013;Sarvan et al, 2017;Leppänen, 2019), one of the three regions in Europe identified with a distinct 7 Be behavior in the surface air (Ajtić et al, 2016(Ajtić et al, , 2017Hernández-Ceballos et al, 2015, 2016. Among these studies, Ajtić et al (2016) analyzed the 7 Be concentration measured in Helsinki, Finland, over 25 years (1987 and pointed out a relatively high number of 7 Be extremes occurring over autumn and winter: more specifically, 10 % of the highest 7 Be concentrations (above the 90th percentile) were observed in the cold season (October-March).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation